Development of a Comprehensive Approach for the Early Diagnosis of Geriatric Syndromes in General Practice - Senn, Nicolas; Monod, Stéfanie (Frontiers in Medicine, 2015)
According to demographic projections, a significant increase in the proportion of the elderly population is anticipated worldwide. This aging of the population will lead to an increase in the prevalence of chronic diseases and functional impairment. This expected increase will result in growing use of the health care system that societies are largely unprepared to address. General practitioners (GPs) are at the front line of this huge epidemiological challenge, but appropriate tools to diagnose and manage elderly patients in routine general practice are lacking. Indeed, while primary prevention and the management of common chronic diseases such as hypertension, diabetes, or cardiac ischemic diseases are routinely and mostly adequately performed in primary care, the management of geriatric syndromes is often incomplete. In order to address these shortcomings, this theoretical work aims to: first develop, based on the best available evidence, a Brief Assessment Tool (BAT) specifically designed for geriatric syndromes identification in general practice; and second, to propose a conceptual framework for the management of elderly patients in general practice that integrates the BAT instrument into the usual care of GPs. To avoid proposing unachievable goals for the care of elderly patients in general practice (for example performing all the best screening tools for geriatric conditions identification and care), this work proposes an innovative way to combine geriatric assessment with the management of common chronic diseases.